2002
DOI: 10.1051/animres:2002002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time of starch supply to the rumen on the dynamics of urea and ammonia net flux across the rumen wall of sheep

Abstract: -The effects of rumen starch fermentation on urea and ammonia net fluxes across the ruminal wall were studied in four Texel wethers (67 ± 1.5 kg BW) fitted with catheters in both ruminal veins and in a mesenteric artery, blood flow probes on ruminal arteries, and a ruminal cannula. They were fed 500 g of orchardgrass hay every 12 h. A dose of 120 g of starch was added directly to the rumen either during the meal or 3 h later. On a daily basis, the time of starch supply did not modify the urea and ammonia net f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…These results are similar to the results from previous studies in rats and rabbits (Tokunaga et al 1989;Oku 1996;Xiao et al 2012). Both in vivo Thorlacius et al 1971;Remond et al 1993Remond et al , 2002von Engelhardt et al 2007) and in vitro (Abdoun et al 2005) studies of the ruminal epithelium suggested SCFA and CO 2 facilitate the transport of urea into the rumen. SCFA might have facilitated the transport of blood urea N into the cecum of the guinea pigs; similar to what has been observed in ruminants.…”
Section: Discussionsupporting
confidence: 90%
“…These results are similar to the results from previous studies in rats and rabbits (Tokunaga et al 1989;Oku 1996;Xiao et al 2012). Both in vivo Thorlacius et al 1971;Remond et al 1993Remond et al , 2002von Engelhardt et al 2007) and in vitro (Abdoun et al 2005) studies of the ruminal epithelium suggested SCFA and CO 2 facilitate the transport of urea into the rumen. SCFA might have facilitated the transport of blood urea N into the cecum of the guinea pigs; similar to what has been observed in ruminants.…”
Section: Discussionsupporting
confidence: 90%
“…This is a typical pattern for ruminal NH3-N rumen pool. It fits the model which usually peaks after feeding followed by a decrease in NH3-N and pH, increase in ruminal VFA and CO2 associated with starch fermentation, accompanied by a decrease in NH3 absorption and a later increase in urea transfer across the ruminal wall (Rémond et al, 2002;Abdoun et al, 2006). The consistently lower NH3-N concentration 2 h after feeding can be linked to the negative DIP balance for CD.…”
Section: Blood Profile and Rumen Parameterssupporting
confidence: 61%
“…The mechanism by which epithelial urea flux is regulated is unknown at present. However, it has been shown that timing of starch feeding relative to roughage feeding affects the ruminal vein extraction of urea (Ré mond et al, 2002). This points to epithelial blood flow as a possible determinant of urea extraction across PDV tissues, because it is only blood passing the epithelia that supply urea to the gastro-intestinal tract.…”
Section: Net Portal Fluxesmentioning
confidence: 99%